1983
DOI: 10.1116/1.582579
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and strain relaxation at the InAs/GaAs(100) heterojunction

Abstract: Transport and strain relaxation in wurtzite InAs-GaAs core-shell heterowires Appl. Phys. Lett. 98, 152103 (2011); 10.1063/1.3579251Competition between strain-induced and temperature-controlled nucleation of InAs/GaAs quantum dots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In the extreme case of InAs on GaAs the transition occurs near 1.5 ML. We have previously shown that the surface stoichiometry is a key factor controlling the growth mode [26][27][28]. Indeed, MBE growth under slightly In-stable conditions totally prevents the 2D-3D transition as confirmed by the RHEED patterns given in Fig.…”
Section: Featuresupporting
confidence: 68%
“…In the extreme case of InAs on GaAs the transition occurs near 1.5 ML. We have previously shown that the surface stoichiometry is a key factor controlling the growth mode [26][27][28]. Indeed, MBE growth under slightly In-stable conditions totally prevents the 2D-3D transition as confirmed by the RHEED patterns given in Fig.…”
Section: Featuresupporting
confidence: 68%
“…In the remaining samples the electron mobility shows a strong decreasing trend with increased V-III ratio. A study of InAs growth on GaAs by MBE has shown that growth carried out under conditions leading to In-stable reconstruction results in higher quality bulk InAs material [15,16]. This finding suggests that lower arsenic to indium ratio will produce InAs crystallites that are closer to stoichiometric, and this accounts for the higher mobility at lower V-III ratios.…”
Section: Resultsmentioning
confidence: 92%
“…5,6 The growth of highly strained semiconductor layer ͑InAs, In x Ga 1Ϫx As͒ onto a substrate ͑GaAs, InP͒ could lead to the spontaneous formation of semiconductor nanometer-scale clusters. [7][8][9][10][11][12][13] Very sharp emission lines from InAs/GaAs heterostructures prepared from this method have been observed recently, [14][15][16] directly representing the ␦-function-like density of states in the zero-dimensional system. P. D. Wang et al 17 studied the optical properties of InAs/ GaAs heterostructures with InAs average layer thickness ranging from 1 Å ͑one-third of a ML͒ to 4 ML grown on ͑100͒ and ͑311͒ surfaces.…”
Section: Introductionmentioning
confidence: 93%